Characterization of composite plates using the virtual fields method with optimized loading conditions - Kashif, Syed Muhammad; Toussaint, Evelyne; Gre´diac, M.; Avril, Ste´phane; Kim, J. H. (Science Direct, 2008)
This paper deals with the direct identification of bending stiffnesses of thin homogeneous anisotropic plates. The idea is to determine the unknown parameters from a single test giving a unique heterogeneous strain field. For the purpose of identification, the virtual fields method (VFM) is used. Here, the VFM is used taking into account two very recent developments: the piecewise construction of virtual fields and the noise minimization effect. Using these new aspects, improvements in terms of result accuracy are shown in comparison to previous studies. These new aspects are used as a tool to grade and to optimize different testing configurations with respect to the location of the applied loading. Some preliminary experimental results are then presented. They are in good agreement with theoretical expectations found in the first part of the study.